Molecular Cloning and Expression an 8-kDa Subunit of Antigen B from G1 strain of Echinococcus granulosus - Hakim AZIZI; Bahram KAZEMI; Mojgan BANDEHPOUR; Mehdi MOHEBALI; Ali KHAMESIPOUR; Mojgan ARYAEIPOUR; Mohammad Bagher ROKNI (Tehran University of Medical Sciences, 2015)
Background: Echinococcosis or hydatidosis is a chronic, zoonotic worldwide infection caused by the larval stage of the dog taeniid tapeworm Echinococcus granulosus. Vaccination has been considered as one of the ways to prevent of hy-datidosis in recent decades. The aim of this study was to construct a pcDNA3.1 eukaryotic expression vector contain-ing the subunit 8-kDa antigen B (Hyd1) of E. granulosus (G1 strain) and investigate its capability to induce protein ex-pression in mammalian cell line, as a basis toward developing a DNA vaccine against hydatidosis. Methods: The coding sequence of HydI was amplified by PCR with the specific PCR primers from pQE/HydI, and then was sub-cloned into pcDNA3.1 plasmid as expression vector. The pcHyd1 plasmid was digested by restriction enzymes and amplified with the specific PCR primers to confirm cloning of this gene in pcDNA3 plasmid. In last step, the sub-cloned gene was expressed in mammalian cell line (NIH 3T3 cells). Result: The subunit 8-kDa antigen B (Hyd1) was successfully sub-cloned in pcDNA3.1 and Hyd1 protein was ex-pressed in eukaryotic cell confirmed by SDS-PAGE and Western blot. Conclusion: Recombinant plasmid of pcDNA3.1 was successfully constructed and express of recombinant Hyd1 protein was confirmed. That is promising step for forthcoming measures on providing vaccine against human and animal hydatidosis.